Assessing the feasibility of using salivary microRNAs as biomarkers to distinguish between chronic stress and childhood trauma in African American young women in an exploratory pilot study - Holliday, Erica; Bagasra, Anisah; Bagasra, Omar; Pandey, Pratima (Frontiers in Psychiatry, 2025)
IntroductionThe current study assessed the impact of self-reported stress measures on microRNA (miRNA) profiles in saliva exosomes. Saliva is one of the most accessible and non-invasive bodily fluids and exosomal miRNAs in saliva could be useful in (1) measuring stress states and (2) distinguishing between individuals suffering from high levels of chronic stress vs. adverse childhood experiences (ACEs). miRNAs are small, noncoding RNAs that act as gene regulators. Several studies have shown differential expressions of certain miRNA in neurological diseases and in stress, post-traumatic stress syndrome (PTSD) and anxiety. Detailed analyses of miRNA expressions and profiling of miRNAs among populations with various exposures to traumatic and life stressors have not been carried out. The goal of our study was to discover miRNAs associated with high chronic stress or childhood trauma.MethodThis study sought to explore miRNA expression in African American young women from a small, southern Historically Black College and University (HBCU). Twelve participants completed the social readjustment rating scale (SRRS), ACEs scale, and saliva collection and were divided into three groups based on ACE and chronic stress score: Low Chronic Stress (LCS; n = 4); High Chronic Stress (HCS; n = 4); High Chronic Stress + High ACEs (HCS+HA; n=4). A custom-made miRNA Taqman-Array tested for fold change in four miRNAs (i.e., miR-19b, miR-187, miR-34a and miR-135-3p).ResultsThere was a significant downregulation of miR-19b (χ2(2, N=12) = 7.42, p < 0.01, η²= 0.915), miR-187 (χ2 (2, N = 12) = 7.36, p < 0.05, η²= 0.598), and miR-34a (χ2(2, N = 12) = 7.42, p < 0.05, η²= 0.60). in both the HCS and the HCS+HA groups vs. LCS. Interestingly, miR-135-3p (χ2(2, N = 12) = 8.00, p < 0.05, η²= 0.67. was upregulated in the HCS group vs. LCS and HCS+LA. Expression for miR-135-3p was not significantly different between LCS + HCS+HA.ConclusionOur analyses shows that miRNA extracted from salivary exosomes can be a reliable biomarker for stress and miR-135a-3p appears to be the most upregulated between LCS and HCS individuals and a potential candidate to corroborate self-reports on self-assessments and predict negative health outcomes. Given that HCS+HA did not show an upregulation of miR-135-3p but had similar expression in the other three miRs compared to HCS group may indicate an adaptive stress response following early life adversity. Further, downregulation in miR-135-3p in individuals with high levels of chronic stress could point to unknown childhood trauma exposure (e.g. closed adoptions, dissociative amnesia, abuse). A major limitation in this study is the small sample size and future directions include determining the predictive validity of these miRNAs in predicting onset of physical and mental health outcomes for early interventions in larger studies.